Severity as a moral qualifier of malady - Carl Tollef Solberg; Mathias Barra; Lars Sandman; Bjørn Hoffmann (BMC Medical Ethics, 2023)
Abstract The overarching aim of this article is to scrutinize how severity can work as a qualifier for the moral impetus of malady. While there is agreement that malady is of negative value, there is disagreement about precisely how this is so. Nevertheless, alleviating disease, injury, and associated suffering is almost universally considered good. Furthermore, the strength of a diseased person’s moral claims for our attention and efforts will inevitably vary. This article starts by reflecting on what kind of moral impetus malady incites. We then analyze how severity may qualify this impetus. We do so by discussing the relationship between severity and need, well-being and disvalue, death, urgency, rule of rescue, and distributive justice. We then summarize our thoughts about severity as a moral qualifier. We conclude that severity is, and should continue to be seen, as a morally significant concept that deserves continued attention in the future.